Conceptual Framework for Growth Triangles (The Pakistan Development Review, 1999)
In recent years, while the significance of regional trade and trading blocs within Asia region (AFTA, APEC, ASEAN, SAARC, EAEC, etc.) has gained considerable interest among the policy-makers and researchers alike, tangible accomplishments, in terms of enhanced economic cooperation and trade liberalisation among the trading blocs, are still muted [Thant et al. (1998), p. 23]. Several reasons and problems have been cited for the limited success of these formal trading blocs, particularly in the Asia region, namely: